Desenvolvimento de procedimentos eletroanalíticos para a determinação simultânea de analgésicos em formulações farmacêuticas e fluidos biológicos empregando o eletrodo de diamante dopado com boro - Santos, Anderson Martin dos (2015)
In this master dissertation, electroanalytical procedures for the simultaneous determination of analgesics paracetamol (PAR) and codeine (COD) and, PAR and tramadol (TRA) in pharmaceutical samples and biological fluids using a cathodically pretreated boron-doped diamond electrode (BDDE) were developed. In the first procedure, the square-wave voltammetry (SWV) was employed for the simultaneous determination of PAR and COD, using as supporting electrolyte 0.2 mol L−1 acetate buffer (pH 4.0), and the analytical curves were linear in the concentration range from 0.2 to 95.8 μmol L−1 for PAR and from 0.2 to 95.8 μmol L−1 for COD, with detection limits (LODs) of 0.018 μmol L−1 and 0.014 μmol L−1, respectively. The second procedure developed for the simultaneous determination of PAR and COD was based on a flow injection analysis with multiple pulses amperometric detection (FIA-MPA), using as transport solution a 0.05 mol L−1 H2SO4 solution. The potential pulse application sequence in function of time was 950 mV / 200 ms (potential where only the PAR oxidation occurs) and 1400 mV / 100 ms (potential where both analytes suffers oxidation (PAR and COD)). The obtained analytical curves show linearity from 0.08 to 100.0 μmol L−1 for PAR and 0.05 to 10.0 μmol L−1 for COD, with LODs of 0.030 e 0.035 μmol L−1 for PAR and COD, respectively. The analytical frequency was estimated as being 90 determinations h−1. After, an electroanalytical procedure using FIA–MPA it was developed a simultaneous determination of PAR and TRA. The potential pulse application sequence in function of time was 850 mV / 200 ms (potential where only occurs the PAR oxidation) and 1600 mV / 100 ms (potential where both analytes suffers oxidation). The obtained analytical curves show linearities between 1.0 to 100.0 μmol L−1 and 0.08 to 10.0 μmol L−1 for PAR and TRA, respectively, and the LOD was 0.030 μmol L−1 for PAR and 0.040 μmol L−1 for TRA. Finally, all developed procedures were employed for the simultaneous determination of these compounds (PAR + COD e PAR + TRA) in pharmaceutical samples, where the obtained results agree with those results obtained using a comparative method (HPLC – High-performance liquid chromatography). These compounds were simultaneously analyzed in synthetic biological fluids (urine and human serum) by addiction and recuperation method, where the recuperations obtained ranged from 90.8 to 108%.